Short Communication: Habitat characterization of Aristolochia baetica L. in Tessala Mount, Western Algeria - HAKEMI ZAHRA; MEHDADI ZOHEIR; CHERIFI KOUIDER; AISSET AMEL (Society for Indonesian Biodiversity, 2018)
Zahra H, Zoheir M, Ali L, Kouider C, Amel A. 2018. Short Communication: Habitat characterization of Aristolochia baetica L. in Tessala Mount, Western Algeria. Biodiversitas 19: 1632-1641. The aim of the current investigation was to study the characterization of the habitat of Aristolochia baetica L., an Ibero-Mauretanian species, present in Tessala Mount (West of Algeria). Twenty-four phytoecological surveys were realized on eight stations (St1-St8) in which the species is present. The floristic inventory allowed us to identify 68 species which are part of the floristic of A. Baetica, distributed in 31 botanical families; 6 biological and 19 biogeographical types. The assessment of edaphic and plant data using correspondence factor analysis (CFA) and hierarchical ascending classification (HAC) showed that A. baetica is a member of plant training of scrublands and grows especially in stations at low heights with a high rate of limestone.